FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN MUSCULOSKELETAL DISORDERS DAN KELELAHAN KERJA PEKERJA PEMILAHAN BUNGA CENGKEH - Ni Made Ayu Wulandari; A.A Istri Diah Indrasuari; Ni Putu Ayu Resitha Dewi; Cokorde Gde Putra Pemayun; I Kadek Dwi Arta Saputra (Bajang Institute, 2024)
In the process of clove flower sorting, occupational health problems can be found, such as working in a standing position for hours, repetitive hand movements in separating clove flowers for more than 8 hours a day, and workers working with non-ergonomic postures that pose risks. This study aims to determine the relationship between internal and external factors with musculoskeletal disorders and work fatigue. Method: This study uses a quantitative research design with an analytical cross-sectional approach. The sampling technique in this study uses total sampling from all 30 clove flower sorting workers. Data collected consists of primary data, and univariate analysis and bivariate analysis using the Chi-square test were performed to determine the relationship. Results: It was found that musculoskeletal complaints, musculoskeletal disorders (MSDs), and work fatigue were significantly higher in relation to age, length of service, working hours, rest time, physical workload, and work posture. Conclusion: Internal and external factors of the respondents are related to musculoskeletal complaints (MSDs) and work fatigue in clove flower sorting workers.